(untitled) (LEARNing Landscapes, 2011)
Why does one enter graduate studies? What does it mean to do research on Indigenous education as an Aboriginal person? What is the significance of attaining a master’s degree? In this paper I speak to how the experience of inquiring into the educational stories of five of my relatives, and into my own lived experiences, helped me understand the importance of stories and the impact of the autobiographical narrative inquiry on myself and my family.